2023
DOI: 10.1177/21676968231168923
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Trait Impulsivity on Suicidality in the Emerging Adult in Kenya

Abstract: Suicidal thoughts and behaviors are complex phenomenon and their relationship to trait impulsivity remains unclear. Although suicidal thoughts and behaviors are common among emerging adults, the availability and quality of data is scarce in countries like Kenya, due to stigmatization and illegality of suicidal behaviors. This research sought to determine the prevalence of suicidal ideation and suicide attempt in emerging adults in Kenya and examine the role of trait impulsivity. Data from 297 undergraduate stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…In the literature, a limited number of studies, indirectly, investigated the relationship between impulsivity and stress. Mwendwa-Karinge et al studied the relationship by focusing on the suicidality of undergraduate students, and they found that the stress factor underlying suicidality is indirectly associated with trait impulsivity [ 10 ]. In another study focusing directly attentional impulsivity, Cavaliere reported that attentional impulsivity is negatively associated with stress-related eating behaviour [ 11 ].…”
mentioning
confidence: 99%
“…In the literature, a limited number of studies, indirectly, investigated the relationship between impulsivity and stress. Mwendwa-Karinge et al studied the relationship by focusing on the suicidality of undergraduate students, and they found that the stress factor underlying suicidality is indirectly associated with trait impulsivity [ 10 ]. In another study focusing directly attentional impulsivity, Cavaliere reported that attentional impulsivity is negatively associated with stress-related eating behaviour [ 11 ].…”
mentioning
confidence: 99%